Security framework of Asynchronous Transfer Mode in Computer Network using Artificial Intelligence - Ali Munther Abdulrahman, Asmaa Abdulazeez Dakhil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
For specific applications, sound is legitimately passed on circumspectly. Video applications are following shrewd, particularly for video on-demand. These moved streams require strong rate mechanized channels between the source and objective, at any rate an earth shattering number of all structures being sifted through today rely on the pack traded Asynchronous Transfer Mode (ATM) movement. In this project author are working on AI Concept. Machine Learning and Artificial Intelligence (AI) are two of the buzzwords of the moment. In financial institutions, there is a lot of focus on emerging technologies, things like chatbots and intelligent processes. But how do AI and Machine Learning apply to the ATM space, and how can they be used to make advancements. Renovate we are continuously looking at the data generated by ATMs and reflecting on what it could be used for – and how. One thing that AI is good at is determining ‘what is normal?’ and this is a key element for the operability of ATMs. This paper fills in as an introduction to ATM, with supplement on its ability to pass on fixed rate stations, and portrays the arrangement of the Cambridge Digital Interactive Television Trial, where Video and Audio on demand are passed on to the Home over ATM. Asynchronous transfer mode was structured in view of cells. This is on the grounds that voice information is changed over to parcels and is compelled to impart a system to blast information (huge bundle information) going through a similar medium. In this way, regardless of how little the voice bundles are, they generally experience full-sized information parcels, and could encounter greatest lining delays. This is the reason all information parcels ought to be of a similar size. The fixed cell structure of ATM implies it very well may be effectively exchanged by equipment without the deferrals presented by steered edges and programming exchanging. This is the reason a few people accept that ATM is the way in to the web data transmission issue. ATM makes fixed courses between two focuses before information move starts, which varies from TCP/IP, where information is isolated into bundles, every one of which takes an alternate course to find a good pace. This makes it simpler to charge information use. Be that as it may, an ATM arrange is less versatile to an abrupt system traffic flood. The ATM gives information interface layer benefits that sudden spike in demand for the OSI's Layer 1 physical connections. It works a lot of like little parcel exchanged and circuit-exchanged systems, which make it perfect for genuine rime, low-inactivity information, for example, VoIP and video, just as for high-throughput information traffic like document moves. A virtual circuit or association must be built up before the two end focuses can really trade information